A Review in Innovation in Ocular Prostheses and Visual Implants: New Biomaterials and Neuro-Implants is the Challenge for the Visual Care - Ospina, Patricia Durán; Díaz, Mayra Cáceres; Plaza, Jhonny Peña (Journal of Ocular Diseases and Therapeutics, 2014)
Objective: To update in new biopolymers and innovations for ocular prostheses and visual implants for visual care. Methodology: The systematic review about biomaterials for ocular prostheses and visual implants was consulted on the following Journals Databases: Investigative Ophthalmology and Visual Science, Nature Eye, Ophthalmology, Br. J. Ophthalmology, Ophthalmic plastic in reconstructive surgery for a total review of 67 articles and 8 e-books were consulted with the following keywords: ocular prostheses and biopolymers, visual and ocular implants, artificial eye. Inclusion criteria: “ocular prostheses”, retinal prostheses systems (RPS) and “visual implants”. Search resources: MEDLINE, PubMed, SciELO, Biblioteca virtual en salud (BVS). Results: The traditional concept of ocular prostheses (ocular, orbital, epithesis, maxillofacial) and visual implants (retinal, optic nerve, cortical, subretinal, epiretinal and cortical implants, artificial silicon retinas and suprachoroidal transretinal stimulation (STS)) among others are changing on now days due to the new advances in technologies and also to the developing of new biomaterials, new microelectrodes and neural devices of several types around the world. Now, real “artificial eyes” are not only the craniofacial, maxillofacial, ocular and orbital prostheses, that replaces an absent eye after an enucleation. But also, new materials such as cryolite glass, gel from cellulose produced by Zoogloea sp., glass, silicone and porous polyethylene, graphene, dental biopolymers among others are being implemented as a materials for heart, eye and other organs implants due to their characteristics to improve good biological compatibility, to be more resistant and to contribute to reduce allergies and improve durability. These implants are used for replacement of the orbital content of the anophthalmic cavities. In addition to this, the existing wearing protocols must be updated, as the three phases model of prosthetic eye wear: establishment of homeostasis deposits builds up, recovery from effects of handling the prosthesis, and the posterior homeostasis´s stabilization for mucus and deposits, must be reduced in a near future by means of surface nanofilm or the inclusion of new biopolymers for fabrication to prevent the adherences and anticipate to immune responses after the implantation of these foreign bodies. Conclusions: The new emerging sciences that are applied to visual sciences will be helpful for the ocular prostheses and visual implant´s users, involving a better performance for fabrication and implantation of these devices. New more biocompatible, resistant materials and the inclusion of microelectrodes for the fabrication of visual implants and also the implementation of the artificial intelligence for the eye have been developed by many researchers around world, because of emerging technologies which have been already patented and that are providing alternatives to patients who have lost their vision, and require visual rehabilitation and in a near future to recover their vision. Additional to the creation of new devices, there are some important processes that take a place such as: Complex biomathematical modeling, new surgical techniques, placement, trial In vivo animal experiments (multielectrode arrays) and In vitro animal experiments (patch clamping, extracellular recording, two-photon imaging) and in the same way, after patient´s process follow up: simulated human psychophysics and some advances have been developed in 3D printers.